Reduction of torque ripple in DTC for induction motor using input-output feedback linearization - Belkacem Sebti (Serbian Journal of Electrical Engineering, 2011)
Direct torque control (DTC) is known to produce fast response and robust control in AC adjustable-speed drives. However, in the steady-state operation, notable torque, flux, and current pulsations occur. In this paper a nonlinear DTC of IM drives is presented based on a Space Vector PWM scheme combined with Input-Output Feedback Linearization (IOFL) technique. The variation of stator and rotor resistance due to changes in temperature or frequency deteriorates the performance of DTC controller by introducing errors in the estimated flux linkage and the electromagnetic torque. As a result, this approach will not be suitable for high power drives such as those used in tractions, as they require good torque control performance at considerably lower frequency. Finally, extensive simulation results are presented to validate the proposed technique. The system is tested at different speeds and a very satisfactory performance has been achieved.